APPRAISAL OF T-INTERSECTION CAPACITY AFTER TRANSFORMATION OF TRAFFIC PRIORITY (Perner's Contacts, 2009)
The paper deals with problem of capacity calculation of T-intersection. There is also referred to change of calculation after transformation of traffic priority. The calculations are made on intersection Nad Porubkou – Rudná (ramp F) in Ostravacity.
Keywords: Intersection; Road Transport; Capacity